MERTK activation drives osimertinib resistance in EGFR-mutant non–small cell lung cancer - Dan Yan; Justus M. Huelse; Dmitri Kireev; Zikang Tan; Luxiao Chen; Subir Goyal; Xiaodong Wang; Stephen V. Frye; Madhusmita Behera; Frank Schneider; Suresh S. Ramalingam; Taofeek Owonikoko; et al. (The Journal of Clinical Investigation, 2022)
Acquired resistance is inevitable in non–small cell lung cancers (NSCLCs) treated with osimertinib (OSI), and the mechanisms are not well defined. The MERTK ligand GAS6 promoted downstream oncogenic signaling in EGFR-mutated (EGFRMT) NSCLC cells treated with OSI, suggesting a role for MERTK activation in OSI resistance. Indeed, treatment with MRX-2843, a first-in-class MERTK kinase inhibitor, resensitized GAS6-treated NSCLC cells to OSI. Both GAS6 and EGF stimulated downstream PI3K/AKT and MAPK/ERK signaling in parental cells, but only GAS6 activated these pathways in OSI-resistant (OSIR) derivative cell lines. Functionally, OSIR cells were more sensitive to MRX-2843 than parental cells, suggesting acquired dependence on MERTK signaling. Furthermore, MERTK and/or its ligands were dramatically upregulated in EGFRMT tumors after treatment with OSI in both xenograft models and patient samples, consistent with induction of autocrine/paracrine MERTK activation. Moreover, treatment with MRX-2843 in combination with OSI, but not OSI alone, provided durable suppression of tumor growth in vivo, even after treatment was stopped. These data identify MERTK as a driver of bypass signaling in treatment-naive and EGFRMT-OSIR NSCLC cells and predict that MRX-2843 and OSI combination therapy will provide clinical benefit in patients with EGFRMT NSCLC.